2003
DOI: 10.1021/ja0291538
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Fumed Silica Particles:  Synthesis, Characterization, and Biomedical Application

Abstract: The preparation, characterization, and preliminary biomedical application of various nitric oxide (NO)-releasing fumed silica particles (0.2-0.3 microm) are reported. The tiny NO-releasing particles are synthesized by first tethering alkylamines onto the surface of the silica using amine-containing silylation reagents. These amine groups are then converted to corresponding N-diazeniumdiolate groups via reaction with NO(g) at high pressure in the presence of methoxide bases (e.g., NaOMe). N-Diazeniumdiolate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
221
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(231 citation statements)
references
References 44 publications
3
221
0
2
Order By: Relevance
“…Zhang et al reported that the addition of a strong base such as sodium methoxide (NaOMe) during NO exposure promotes the deprotonation of the secondary amine nitrogen, thereby shifting the reaction equilibrium toward N-diazeniumdiolate formation. 24 Furthermore, the sodium ion serves as a countercation to stabilize the anionic N-diazeniumdiolate structure of 3 (see Supporting Information). When NaOMe was employed in this work, the conversion efficiencies increased more than 10-fold with typical yields of 54 -100% (see below for details).…”
Section: Synthesis Of N-diazeniumdiolate-modified Silane Monomersmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al reported that the addition of a strong base such as sodium methoxide (NaOMe) during NO exposure promotes the deprotonation of the secondary amine nitrogen, thereby shifting the reaction equilibrium toward N-diazeniumdiolate formation. 24 Furthermore, the sodium ion serves as a countercation to stabilize the anionic N-diazeniumdiolate structure of 3 (see Supporting Information). When NaOMe was employed in this work, the conversion efficiencies increased more than 10-fold with typical yields of 54 -100% (see below for details).…”
Section: Synthesis Of N-diazeniumdiolate-modified Silane Monomersmentioning
confidence: 99%
“…On the basis of monitoring the amount of NO release, the concentration of N-diazeniumdiolate species (C diaz ) at any given time may be determined. 24 The dissociation kinetics of two representative N-diazeniumdiolates derived from AEAP3 and DET3 are shown in Figure 3. Plots of the natural logarithm of the N-diazeniumdiolate concentration (ln C diaz ) versus time yielded a linear relationship, with R 2 values typically ≥0.995 for all N-diazeniumdiolates examined (indicating first-order kinetic behaviors in all cases).…”
Section: Dissociation Kinetics Of N-diazeniumdiolate-modified Silane mentioning
confidence: 99%
See 2 more Smart Citations
“…The first NO-releasing particles with covalent modification was reported by Zhang et al [83] Non-toxic amorphous fumed silica particles (200-300 nm in diameter) were tethered with aminecontaining silylation reagents followed by diazeniumdiolation. The diazeniumdiolated fumed silica particles released NO under physiological conditions via primarily the proton-driven dissociation associated with negligible thermal dissociation.…”
Section: Silica Particlesmentioning
confidence: 99%